Design of REST API for Local Public Transportation Information Services in Malang City - Kharisma, Agi Putra; Pinandito, Aryo (Faculty of Computer Science (FILKOM) Brawijaya University, 2017)
Abstract.Utilization of information technology in the field of public transportation has been proven in improving the quality of public transportation services. The availability of information technology that supports public transportation in Malang city is still limited. An effort is required to encourage the availability of information technology that support public transportation in Malang city. This research attempts to propose a draft proposal of REST API designed for supporting information about public transportation services in Malang city. The result of this research showed that the REST API should provide a search facility to find proper service mode of transportation, cost estimation, time estimation, calling or booking a public transportation, a list of all the modes of transportation that exist, as well as detailed information on a mode of transport in which includes the name of public transportation, index of comfortability, index of security, index of safety, index of privacy, index of availability, index of accessibility index, and route.Keywords: Transportation, Public Transportation, API, REST, Service-Oriented Architecture, Web Service.